Hallucinations and Delusions as Low-Quality Attributions: Influencing Factors and Proposal for Their Analysis - Rodríguez-Testal, Juan F.; Senín-Calderón, Cristina; Moreno, Rafael (Frontiers in Psychology, 2021)
Hallucinations and delusions, in keeping with the distress accompanying them, are major features in the diagnosis of psychosis in international classifications. In spite of their human and clinical importance, the concepts are unclear. The distinction between hallucinations and delusions in terms of perception-thought is not precise enough, causing problems in analyzing the patient’s words. Nor are the differentiations or variations within each precise enough. Continuing the long clinical tradition discussing the distinction between hallucinations and delusions while assuming their similarities, this study poses a concept integrating the two phenomena as attributions people make about themselves and their settings. Then the elements of any attribution can be used as guides for structuring significant literature on both and reduce analytical ambiguity. Such attributions make more sense within the structure of two-way relationships with factors in a person’s own framework and setting. This structure is described with its variables and relationships as a guide to assessment, follow-up and intervention. Two checklists are provided for orientation.